Determinants of inflation: Evidence from ASEAN-5 countries - Farah Dina, Zakaria (2016)
Topic involving inflation has generated an enormous volume of literature and heated debate in recent years. It is important to study inflation because the consequences of inflation is terrible. By explaining inflation, different school of thought view the contrast cause and have different policies for fighting inflation. This study examines the relationship between selected independent variable towards inflation and theory that can explain inflation in ASEAN-5 countries using panel data analysis. This study used panel data spanning from year 1990 to 2014. A panel data approach was used to straighten out the time invariant country-specific effect and to reveal the relationship between the important variables across time. The results presented that fixed effect model was appropriate over the random effect models in this inflation model studied. Interestingly, the variables, namely wages, import, interest rate and gross domestic product were found to be significant determinants of inflation in ASEAN-5 countries. But, only money supply found to be insignificant by explaining the inflation in this sample of study. Based on these results, this study support the Post Keynesians view of inflation and several policy implications and recommendations were suggested.